133k views
4 votes
Please help with this question ​

Please help with this question ​-example-1
User Ezra Chu
by
5.6k points

2 Answers

4 votes

Since, OA is perpendicular to OC


m\angle A OC= 90 \degree \\ m\angle AOB \: + m\angle BOC = 90 \degree \\ (6x - 12) \degree + (3x + 30) \degree = 90 \degree \\ 6x + 3x + 30 - 12 = 90 \degree \\ 9 x + 18 = 90 \\ 9x = 90 - 18 \\ 9x = 72 \\ x = (72)/(9) \\ x = 8 \degree


m\angle \: AOB = 6x - 12 \\ m\angle \: AOB = 6(8) - 12 \\ m\angle \: AOB = 48 - 12 \\ m\angle \: AOB = 36 \degree

User Dhir Pratap
by
4.6k points
2 votes

Explanation:

m< AOC = 90°

m< AOB +m<BOC = 90°

6x-12+3x +30 = 90°

9x +18° = 90°

9x = 90- 18° = 72°

x = 8°

m<AOB =6(8)-12 = 48-12 = 36°

User S B
by
5.3k points